PD-1 Expression Status on CD8+ Tumour Infiltrating Lymphocytes Associates With Survival in Cervical Cancer - Fan, Peiwen; Li, Xi; Feng, Yaning; Cai, Hongchao; Dong, Danning; Peng, Yanchun; Yao, Xuan; Guo, Yuping; Ma, Miaomiao; Dong, Tao; Wang, Ruozheng (Frontiers in Oncology, 2021)
Despite the expansion of PD-1 checkpoint blockade to multiple types of cancer, whether the programmed cell death 1 (PD-1) expression status on CD8+ tumour infiltrating lymphocytes (TILs) could be a prognostic factor in cervical cancer is still unclear. In this study, we performed ex vivo phenotypic analysis of PD-1 expression on CD8+ TILs by flow cytometry from 47 treatment-naïve cervical cancer patients. With a median follow-up of 26.1 months (95% confidence interval [CI], 24-28.2 months), we then linked the quantitative cellular expression results to progression-free survival and overall survival. Based on the intensity of PD-1 expression, we further categorised the cervical cancer patients into PD-1high expressers (29.8%, 14/47) and PD-1low expressers (70.2%, 33/47). Multivariate analysis revealed that PD-1high expressers are correlated with early recurrence (HR, 5.91; 95% CI, 1.03-33.82; P= 0.046). Univariate analysis also demonstrated that PD-1high expressers are associated with poor overall survival in cervical cancer (HR, 5.365; 95% CI, 1.55-18.6; P=0.008). Moreover, our study also demonstrated that CD8+/CD4+ TIL ratio and HPV infection status are risk factors for early relapse and mortality in cervical cancer patients. In conclusion, this study confirms that PD-1 expression status is an independent prognostic factor for progression free survival in cervical cancer. These findings could be important in predicting the relapse of cervical cancer as a cellular diagnosis method and could be important knowledge for the selection of prospective PD-1 blockade candidates.